Pengaruh Whistleblowing System Dan Budaya Organisasi Terhadap Pencegahan Kecurangan Di Kantor Imigrasi Kelas I TPI Bandung - Yulientinah, Dewi Selviani; Mukhlisha, Vidya Haifa (LAND JOURNAL, 2024)
Immigration Office Class I TPI (Immigration Checkpoint) Bandung is a government unit under the Ministry of Law and Human Rights and holds a substantial significance in the administration of immigration affairs and supervision services. Immigration office has a form of supervision to prevent all forms of fraud or violations in the form of whistleblowing systems and supervision in the form of attitudes and rules of "organizational culture" in the implementation of its work. By using associative quantitative research methods using a survey in the form of primary data, namely a questionnaire on 39 respondents. The purpose of the research was to identify the partial and simultaneous impact of the whistleblowing system and organizational culture on fraud prevention efforts at Bandung Class I Immigration Office. Employing methods of data analysis utilizing data quality tests, correlation analysis, multiple linear regression analysis, and also hypothesis analysis using the help of SPSS ver.27. The findings indicated that the whistleblowing system had limited impact on deterring fraud, whereas the organizational culture demonstrated a favorable influence on fraud prevention. Simultaneously, whistleblowing system variables and organizational culture affect fraud prevention.